2015
DOI: 10.1155/2015/785638
|View full text |Cite
|
Sign up to set email alerts
|

UP3005, a Botanical Composition Containing Two Standardized Extracts ofUncaria gambirandMorus alba, Improves Pain Sensitivity and Cartilage Degradations in Monosodium Iodoacetate-Induced Rat OA Disease Model

Abstract: Osteoarthritis (OA) is a multifactorial disease primarily noted by cartilage degradation in association with inflammation that causes significant morbidity, joint pain, stiffness, and limited mobility. Present-day management of OA is inadequate due to the lack of principal therapies proven to be effective in hindering disease progression where symptomatic therapy focused approach masks the actual etiology leading to irreversible damage. Here, we describe the effect of UP3005, a composition containing a proprie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…As a result, alternative treatments that offer a superior safety profile such as plant-based dietary supplements have recently become the focus of attention in OA research [10,11] . For instance, medicinal plants containing phenolic compounds reportedly have a protective effect against the progression of OA as well as alleviating OA pain [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, alternative treatments that offer a superior safety profile such as plant-based dietary supplements have recently become the focus of attention in OA research [10,11] . For instance, medicinal plants containing phenolic compounds reportedly have a protective effect against the progression of OA as well as alleviating OA pain [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, major parts of mulberry trees that are used are the leaves and fruits, while the other parts are left unused. This plant has been reported to have anti-nociceptive, anti-inflammatory and antioxidant activities with these pharmacological properties derived from extracts of the leaves [13,14] , twigs [15] and root barks [12,15,16] . However, little attention has been paid to the stem, despite the fact that it has a much higher content of oxyresveratrol compared with twigs and leaves, respectively [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Diels-Alder adducts and prenylated flavanones isolated from the root bark of M. alba showed cytotoxic activity against human tumor cells [ 13 ]. In another study, a composition containing a blend of standardized extracts from Uncaria gambir leaves and M. alba root bark was reported to be useful as an alternative therapy for alleviating osteoarthritis and its associated symptoms [ 14 ]. Kim et al [ 15 ] reported that extracts from M. alba leaves and fruits were able to reduce cognitive deficits in mice induced by the high-fat diet.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, pharmacological therapies, with anti-inflammatory and chondroprotective effects, aim at reducing pain and preserving matrix integrity, thus improving the patient’s joint activity and quality of life. Recently, several studies have suggested a potential adjuvant role for natural extracts, such as curcumin, resveratrol, pomegranate, as well as genistein and soy protein, on OA progression, in terms of moderating chondrocyte inflammation and following cartilage injury resulting in the improvement of joint pain [ 5 , 6 ]. Moreover, the traditional use of Harpagophytum procumbens (Burch.)…”
Section: Introductionmentioning
confidence: 99%